The Government of Indonesia's Policy Towards the Triple Planetary Crisis in the Environment and Sustainable Development Agenda in the Perspective of Environmental Law (International Journal of Environmental Sciences, 2025)
The environment is a vital boon that now faces serious threats due to industrialization, pollution and climate change. Indonesia, as a country of megabiodiversity, is experiencing great pressure on the sustainability of its natural resources. Although it has regulations such as Law No. 32 of 2009 on Environmental Protection and Management, Implementation Challenges are still very large. The Triple planetary crisis-climate change, pollution, and biodiversity loss carries significant ecological, social, and economic impacts. A clear example is the shrinking of glaciers in Papua and the destruction of primary forests due to industrial and mining activities. This study uses normative juridical methods with a legislative, conceptual, and comparative approach to other countries such as the European Union and Costa Rica. The first discussion highlighted that although Indonesia has a complete legal framework, implementation of environmental policies is still hampered by the weak legal binding power of strategic documents such as IBSAP, overlapping authority between the central and regional levels, as well as the lack of Cross-Sector Coordination and consistent funding. The second discussion focused on the “Environment and Sustainable Development” agenda by the Ministry of Environment and Forestry (KLHK), including the preparation of the 2025-2055 Environmental Protection and Management Plan (RPPLH) and the 2024 party. MoEF also cooperates with international organizations such as UNEP and IUCN in strengthening environmental monitoring and conservation. Although policies have been designed with a clear direction, the gap between their formulation and implementation remains a major obstacle in environmental governance in Indonesia.